The impact of a training field in Lake Al-Razzaza to develop the strength of the legs and arms for young boxers - reda, Hussein; Opayes, Muwafaq (Journal of Physical Education, 2023)
By observing the first researcher, he found that there is some weakness in the physical capabilities, including the strength distinguished by the speed of the legs and arms, and this affects the boxer's ability to continue in the fight, especially at the end of the last round.  For young boxers, the research aims to identify the effect of a training field in Lake Razzaza to develop the strength characteristic of speed for the legs and arms of young boxers, and it is assumed that there are statistically significant differences between the pre and post tests.  Selection of the research community of young boxing players in the Karbala Governorate clubs, whose number is (4) clubs, and the research sample was chosen randomly, and they are the youth players of the Iraq Sports Club in Karbala Governorate, whose number is (12) players with weights (60-64 kg), where the sample is divided into two groups  (experimental and control) and that the exercises prepared by the researcher affected the development of strength characterized by the speed of the legs and arms of boxing players weighing (60-64) in the youth category. The researchers recommended the use of the training field and special exercises for other samples, levels and games